Barriers to access and uptake of antiretroviral therapy among HIV-positive men who have sex with men in Hanoi, Vietnam: from HIV testing to treatment. Issue 8 (3rd August 2017) - Bui, Hao T. M.; Le, Giang M.; Mai, Anh Q.; Zablotska-Manos, Iryna; Maher, Lisa
Abstract: Little is known about the experiences of Vietnamese men who have sex with men in accessing HIV testing and treatment. We aimed to explore barriers to access and uptake of antiretroviral therapy (ART) among HIV-positive men who have sex with men in Hanoi. During 2015, we conducted qualitative interviews with 35 participants recruited using snowball sampling based on previous research and social networks. Key individual impediments to ART uptake included inadequate preparation for a positive diagnosis and the dual stigmatisation of homosexuality and HIV and its consequences, leading to fear of disclosure of HIV status. Health system barriers included lack of clarity and consistency about how to register for and access ART, failure to protect patient confidentiality and a reticence by providers to discuss sexual identity and same-sex issues. Results suggest fundamental problems in the way HIV testing is currently delivered in Hanoi, including a lack of client-centred counselling, peer support and clear referral pathways. Overcoming these barriers will require educating men who have sex with men about the benefits of routine testing, improving access to quality diagnostic services and building a safe, confidential treatment environment for HIV-positive men to access, receive and remain in care.